Developing a Choice-Based Digital Fiction for Body Image Bibliotherapy - Wilks, Christine; Ensslin, Astrid; Rice, Carla; Riley, Sarah; Perram, Megan; Bailey, K. Alysse; Munro, Lauren; Fowlie, Hannah (Frontiers in Communication, 2022)
Body dissatisfaction is so common in the western world that it has become the norm, especially among women and girls. "Writing New Body Worlds" is a transdisciplinary research-creation project that aims to address these issues by developing an interactive digital fiction for body image bibliotherapy. It is created with the critical co-design participation of a group of young women and non-binary individuals (aged 18-25) from diverse backgrounds, who are representative of its intended audience. This paper discusses how our participant research influenced the creative development of the digital fiction, its characters and its novel ludonarrative design. It theorizes how the specific affordances of a choice-based interactive narrative, that situates the reader-player in the mind of the fictional protagonist, may lead to enhanced empathic identification and agency and, therefore, a more profoundly immersive and potentially transformative experience. This process of "diegetic enactment" is where we postulate the therapeutic value lies via an extradiegetic feedback loop which may induce the reader-player to reflect upon, and perhaps subtly alter, their own body image.